Interdisciplinary Study of a 15th-Century Byzantine Embroidery Fragment from St Elisabeth’s Cathedral in Košice (Slovakia) - Eva Hasalová; Andrej Krivda; Alena Piatrová (Religions)
This study investigates a Byzantine embroidery fragment found in the Cathedral of St Elisabeth in Košice, Slovakia, which is believed to come from a 15th-century epitrachelion. Through interdisciplinary research, including art historical analysis, archival studies, and material research, the embroidery was identified as a rare example of Byzantine liturgical textile art in Slovakia. The iconography includes Archangel Gabriel and four Eastern Church Fathers. Comparative studies suggest possible origins in Greek or Romanian monastic workshops. Despite the information provided by radiocarbon dating and stylistic comparisons, the embroidery’s precise provenance and historical context invite further research.